2016
DOI: 10.1177/1535370216640942
|View full text |Cite
|
Sign up to set email alerts
|

Immobilized liquid layers: A new approach to anti-adhesion surfaces for medical applications

Abstract: Surface fouling and undesired adhesion are nearly ubiquitous problems in the medical field, complicating everything from surgeries to routine daily care of patients. Recently, the concept of immobilized liquid (IL) interfaces has been gaining attention as a highly versatile new approach to antifouling, with a wide variety of promising applications in medicine. Here, we review the general concepts behind IL layers and discuss the fabrication strategies on medically relevant materials developed so far. We also s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
99
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(101 citation statements)
references
References 67 publications
2
99
0
Order By: Relevance
“…The same authors also demonstrated higher number of adhered bacteria cultured under dynamic conditions in comparison to the static conditions. [98] An excellent review about antiadhesion properties of SLIPS for medical applications including antibacterial and antithrombogenic uses of SLIPS has been recently published by Sotiri et al [15] SLIPS based on medically relevant materials (such as expanded polytetrafluoroethylene and perfluoroperhydrophenanthrene) was prepared, coated onto the implant surface, and then studied in a rat model. [95] The prepared SLIPS showed good in vivo stability and could enable bacterial elimination at the implant surface, while showing low innate immune response as well as reduced inflammatory capsule formation.…”
Section: Cell-repellent and Antibiofouling Slipsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors also demonstrated higher number of adhered bacteria cultured under dynamic conditions in comparison to the static conditions. [98] An excellent review about antiadhesion properties of SLIPS for medical applications including antibacterial and antithrombogenic uses of SLIPS has been recently published by Sotiri et al [15] SLIPS based on medically relevant materials (such as expanded polytetrafluoroethylene and perfluoroperhydrophenanthrene) was prepared, coated onto the implant surface, and then studied in a rat model. [95] The prepared SLIPS showed good in vivo stability and could enable bacterial elimination at the implant surface, while showing low innate immune response as well as reduced inflammatory capsule formation.…”
Section: Cell-repellent and Antibiofouling Slipsmentioning
confidence: 99%
“…Some important and related papers could not be cited due to the length limitations. We also refer readers to several excellent reviews covering applications of SLIPS for heat transfer and condensation, [14] antibiofouling properties, [15] antiicing properties [16] as well as medically relevant applications. [17]…”
mentioning
confidence: 99%
“…[2] Slippery liquid-infused porous surfaces (SLIPS), inspired by the carnivorous Nepenthes pitcher plant, were recently introduced as a new approach to prevent bacterial biofouling in both industrial and medical applications without the need for administering antibiotics. [3][4][5] This approach represents a paradigm shift in materials science, where instead of a solid surface, bacteria are presented with an inherently dynamic and self-healing immobilized liquid (IL) layer that is held in place by a chemically matched substrate. [3,6,7] Epstein et al were the first to demonstrate that the presence of an IL layer of fluorinated oil on ePTFE significantly reduced biofilm coverage of S. aureus and E. coli (by 97.2% and 96%, respectively) after 48 hours of growth under static conditions, compared to ePTFE without an IL layer.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, various polymeric materials have been investigated and tested as potential anti-adhesion barrier films, including nanosheets, 11 polyvinyl alcohol (PVA)/gelatin membranes, 12 polycaprolactone film, 13 photocrosslinkable gellan gum film, 14 silver nanoparticles-loaded poly(l-lactide) fibrous membranes, 15 chitosan-polyvinyl pyrrolidone film, 16 and immobilized liquid layers. 17 Despite these efforts, the development of drug-loaded anti-adhesion film has been limited. Chen et al 18 were the only research team to propose a silver nanoparticle/ ibuprofen-loaded poly(l-lactide) fibrous membrane and evaluate its anti-infection and anti-adhesion effects.…”
Section: Introductionmentioning
confidence: 99%